Analysis of the Effectiveness of Wordwall Media Use on Science Learning Outcomes in Elementary Schools - Rizkye Lestari; Rohmani Rohmani (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to evaluate the effectiveness of using wordwall media on science learning outcomes at the primary school level. This research is important to explore the use of interactive technology in improving student understanding and academic achievement in science lessons. Method: This study aims to evaluate the effectiveness of using wordwall media on science learning outcomes at the primary school level. This research is important to explore the use of interactive technology in improving student understanding and academic achievement in science lessons. Results: The analysis showed that using Wordwall media significantly improved science learning outcomes and learning motivation and created a more interactive and fun learning atmosphere for students. The advantages of Wordwall include active student engagement, increased information retention, personalized learning, collaboration, and real-time feedback. Several studies have shown an increase in the average student score after using Wordwall and increased student activeness and enthusiasm in following the learning process. Novelty: The novelty of this study lies in exploring the specific use of Wordwall in the context of science learning in elementary school and its impact on improving student learning outcomes. Although Wordwall has been widely researched in education in general, this study provides new insights into how this interactive media can effectively improve the quality of science learning at the primary school level and provides recommendations for integrating technology in science teaching.